Our challenging to understand non-genetic effect in addition to genetic one on dento-craniofacial morphogenesis in spontaneous cleft lip/palate mouse model from the standing point of pediatric dentistry - Kazuaki Nonaka (Elsevier, 2009)
Cleft lip with or without cleft palate is the most common congenital anomaly in craniofacial complex, which is our target to deepen our understanding toward a molecular mechanism of dento-craniofacial morphogenesis. The hypothesis that the maternal effects in addition to the genetic ones play important roles on the dento-craniofacial morphogenesis in mice has been tested based on each developmental stage. Firstly, the maternal effects on the intrauterine craniofacial development in the mouse fetus were examined by means of embryo transfer technique, skeletal staining and cephalometry, indicating that the maternal effects were one of important factors on the intrauterine craniofacial morphogenesis of CL/Fr mice. Secondly, when the molecular nature of the maternal effects is elucidated, maternally derived growth factors may play important roles on mouse fetus development. Bone morphogenetic protein 4 (BMP4) and epidermal growth factor (EGF) function antagonistically, yet are coupled in the regulation of initial chondrogenesis. Smad1 serves as a point of convergence for the integration of two different growth factor signaling pathways during chondrogenesis in the mouse fetal mandible. Lastly, transforming growth factor-beta3 (TGF-β3) promoted fusion of cleft lip in the mouse fetus through the molecular pathways. In fact, microsurgical repair of cleft lip in the fetus that produced scarless fusion is mediated by TGF-β3 regulation of mesenchymal cell proliferation and migration at the site of repair. In addition, TGF-β3 promoted cell proliferation and angiogenesis in lip mesenchymal tissues. These events lead to enhancement of the lip fusion in the presence of TGF-β3. In neonatal mouse, application of exogenous TGF-β3 to decrease type I collagen accumulation and consequential scar formation provide the opportunities for the clinical augmentation of scar reduction after cleft lip repair. These findings indicate that the environmental factors provided by the dams cannot be ignored in the etiology of a craniofacial anomaly and/or development in the mouse model in addition to genetic ones.